2006
DOI: 10.1080/00365540500400944
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative analysis of Streptococcus pneumoniae urinary antigen: Kinetics of antigen titers and severity of diseases

Abstract: Detection of urinary antigen by a rapid immunochromatographic membrane test (Binax NOW) was widely accepted as a powerful tool for diagnosis of Streptococcus pneumoniae pneumonia. This is a qualitative kit, so the value of quantitative analysis of urinary antigen, especially correlation of antigen titers and severity of diseases, remained to be determined. We examined semi-quantitative antigen titer in urines collected from urinary antigen-proven S. pneumoniae pneumonia on admission, and analyzed the kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…However, the time to positive reaction and the intensity of reaction band were not influenced by the urinary gravity. The findings were also in agreement with a report by Tateda et al, 4 who suggested that the fold difference between severe and non-severe groups could not be achieved by urinary concentration under normal physiological status.…”
supporting
confidence: 93%
“…However, the time to positive reaction and the intensity of reaction band were not influenced by the urinary gravity. The findings were also in agreement with a report by Tateda et al, 4 who suggested that the fold difference between severe and non-severe groups could not be achieved by urinary concentration under normal physiological status.…”
supporting
confidence: 93%
“…The current findings demonstrate a significant correlation between the test score and disease severity. These observations are in accordance with those of Tateda et al 11 In their study, serial two-fold dilutions of urine were used for antigen testing, and the final dilution that was positive for antigen was recorded as the maximum dilution factor. They have noted that severe cases of S. pneumoniae pneumonia have higher values of maximum dilution factors than those with non-severe disease.…”
Section: Discussionsupporting
confidence: 55%
“…More recently, researchers have developed a new semi-quantitative urinary antigen test to correlate the kinetics of the antigen titers with disease severity. 11 It has been proposed that the amount of pneumococcal antigen present in the urine is related to the magnitude of the bacterial load in the lungs.…”
mentioning
confidence: 99%
“…Other studies testing CAD kit sensitivity and specificity in blood cultures reported a range of 79 to 87% for sensitivity and a range of 83 to 97% for specificity (17,28,31). While these detection rates are high, the CAD kit presents some disadvantages, including false-positive results due to pneumococcal colonization, particularly among children, and long-lasting positive results after antibody treatment (32,33). Therefore, other detection methods for rapidly identifying pneumococcal pneumonia have been developed by several laboratories.…”
Section: Discussionmentioning
confidence: 99%